TOOLS TO ENSURE THE PREVENTION OF CONTRAVENTIONS - Elena Emilia ȘTEFAN (Challenges of the Knowledge Society)
Nowadays, the most common form of law infringement is contravention. The Romanian contravention law was improved at the end of 2017 by a legislative novelty regulating the instruments to ensure the prevention of contraventions. The contraventions provided in this administrative act are diverse and it is interesting that despite this, the law maker provides in many cases the application of a penalty, namely the warning, which is then followed, as the case may be, by the application of a measures plan, limited in time. Furthermore, the offenders will not be pardoned every time, but only once, provided that they fulfill the obligations provided by the measures plan and within the deadline established by the official examiner. This law would have remained only at the stage of intention and without application if the executive had not adopted the administrative act identifying the contraventions contemplated by it, but once the respective Government resolution has been adopted, we can only wait for the time to see the effectiveness of it application. This is why, in this study, we will analyze this topic by being of great interest and adapted to social realities. By being a legislative novelty for the national law system, the scientific research that we performed is mainly focused on the legislation and the doctrine.